The Heidelberg Catechism: elements for a theology of care - F. de Lange (Acta Theologica)
This article proposes a fresh reading of the Heidelberg Catechism from the perspective of an ethics of care, a new paradigm of doing ethics, strongly influenced by feminist philosophy. In its anthropology, this approach in ethics emphasizes human relationality, mutual dependency and vulnerability. Though there are strong affinities with theological anthropology, the ethics of care still lacks a theological framework. The thesis argued here, is that the Heidelberg Catechism offers essential elements for a “theology of care”. It describes 1. God as a caring, ‘mothering” God; 2. human beings as having care as their essence and divine vocation; and 3. the relationship between God and human beings as a relationship of mutual care. The care perspective in the Heidelberg Catechism is limited, however, because it does not give a full account of the open endedness of the relationship between God and humanity.